Synthesis of (-)-galantinic acid via iterative hydrolytic kinetic resolution and tethered aminohydroxylation - Dubey, Abhishek; Kauloorkar, Shruti Vandana; Kumar, Pradeep (Tetrahedron, 2010)
A new synthetic strategy for (-)-galantinic acid is reported using iterative hydrolytic kinetic resolution and tethered aminohydroxylation as the key steps. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: 1; 2-Aminoalcohol; 3-Diol; Iterative hydrolytic kinetic resolution; selectivity; Tethered aminohydroxylation

Stereoselective synthesis of (-)-galantinic acid - Dubey, Abhishek; Harbindu, Anand; Kumar, Pradeep (Synthesis-Stuttgart, 2011)
An efficient and highly concise synthesis of (-)-galantinic acid has been achieved using an asymmetric allylation reaction of Garner's aldehyde.
Keywords: Amino alcohol; Chiral pool; iterative asymmetric allylation; Oxidation; stereoselective synthesis